The Relationship Between Self-Focus and Social Anxiety Disorder - Ren, Jiaxin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
An examination of the severe effects that social anxiety disorder (SAD) has on people is presented in this paper. Particular attention is paid to the condition’s early start and modest heredity. The prevalence of seasonal affective disorder (SAD) is highlighted by the fact that it is the fourth most prevalent mental ailment, and it often occurs in conjunction with other diseases. An increasing level of self-focused attention (SFA) has been connected to an increase in social anxiety, which highlights the significant role that SFA plays in the development of social anxiety disorder (SAD). Symptom reduction treatments that are helpful include cognitive therapy and exposure therapy, both of which target SFA. These interventions are considered as useful techniques for reducing symptoms. When it comes to alleviating symptoms of seasonal affective disorder (SAD), in vivo exposure treatment has been shown to be more effective than virtual reality exposure therapy. The review highlights the need of doing further research in order to determine the most effective therapy options and emphasizes the complexity of the societal costs associated with the treatment of SAD. It is intended that the strategies described in the text for lowering the symptoms of social anxiety via treatments that target self-focused attention may serve as a source of inspiration for intervention programs that are designed to alleviate the symptoms of social anxiety.